Effect of paddy residue management techniques on yield of wheat crop and its attributes - Sangwan, Vikramaditya; Deswal, Surinder (Ecological Questions, 2022)
The research study deals with the results of the yield and yield attributing characters of the wheat crop corresponding to the nine different treatments (T-1 to T-9) of paddy residue management. The wheat yield accounts for the grain yield and straw yield while the wheat yield attributing characters include the spike length, grains per spike, grain test weight, etc. The results of these pertains to the data collected and analysed from the two consecutive years of field experimentation employing various treatments and replications of paddy stubble management. The resultant data of different parameters (yield and its attributing characters) from various treatments carried out through the two years of field experiments is tabulated in the Table 1 and Table 2 for effective discussion of results. The results suggested that the combined use of SMS (straw management system) mounted combine harvester, happy seeder and decomposer provides the best way to manage paddy residue, thereby yielding good yields of succeeding wheat crop to the farmers.